Analisis Kinerja Simpang Empat Bersinyal Pada Jalan Raya Pendem Menggukan PTV Vissim - Mendonca, Natalino; Oktaviastuti, Blima; Arifianto, Andy Kristafi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Transportation facilities play an important role in human life. The existence of human interests that always require mobilization to support activities in daily life, makes it inseparable from transportation, especially roads. Therefore, the road is the easiest means of transportation to move from one place to another. The existence of diverse activities has an effect on increasing transportation needs which results in various problems. In the development process, cities are strategic locations for the creation of population growth rates. In Malang City, many people come for shopping, school, and work. This makes the government continue to develop its territory accompanied by various problems that are increasing every year, especially road transportation problems. Some of these problems include traffic congestion. Based on this background, this study aims to determine the performance of the four-signal intersection on Pendem Street, Malang District. The research design in this study uses quantitative methods with descriptive research types. Based on the results of the research, the results of the performance of the four-signal intersection include: (1) Traffic volume of the West arm 680.45, North 106.55, South 421.2, and East 721.5; (2) Capacity (C) of the North arm 266.4, East 280.4, South 210.3, and West 280.4; (3) Degree of saturation of the West arm 2.426, North 0.399, South 2.002, and East 2.573; (4) Queue length of the West arm 152.52, North 3.94, East 125.72, and South 93.69; (5) West arm stalled vehicle ratio 1.360, North 2.027, South 2.686, and East 1.781; (6) Intersection average delay 299; (7) Intersection road level of service F (very bad); (8) Data analysis using PTV Vissim obtained the level of service on the West arm F (very bad), North B (good), East E (bad), and South F (very bad).